Relationship Between Parent's Motivation And Compliance In Giving Anti-Virus Medicines To HIV Patients - Dwi Rahmawati, Ary; Ira Handian, Feriana; Maria, Lilla (Green Publisher, 2022)
HIV attacks the sufferer's immune system and if coupled with prolonged psychosocial spiritual stress will accelerate the occurrence of AIDS, and even increase the mortality rate. AIDS is incurable. Giving ARV is to suppress the amount of virus (viral load). The purpose of the study was to motivate parents with parental compliance in giving their children anti-HIV drugs. This research is a quantitative method with used purposive sampling, cross sectional technique, 41 respondents were parents or caregivers of children with HIV patients who were taking ARV treatment. The results showed that the level of motivation of parents or caregivers in giving ARV drugs was sufficient 60.98% and Parental Compliance with HIV Drugs was compliant with 73.17%. Based on the Spearman Rank statistical test, the correlation value (r) is 0.372 and the p value is 0.017. P value < (0.05. It is hoped that the officers will improve the provision of health education about treatment and the impact of stopping treatment for patients with the method of giving leaflets to each respondent who comes to take medication so that it can be spread evenly.